Last day on earth : a portrait of the NIU school shooter - Vann, David (Winner of the Associated Writing Programs award for creative nonfiction., 2011)
On Valentine's Day 2008, Steve Kazmierczak killed five and wounded eighteen at Northern Illinois University, then killed himself. But he was an A student, a Deans' Award winner. How could this happen? CNN could not get the story. The Chicago Tribune, Washington Post, and all others came up empty because Steve's friends and professors knew very little. He had reinvented himself in his final five years. But David Vann, investigating for Esquire, went back to Steve's high school and junior high friends, found a life perfectly shaped for mass murder, and gained full access to the entire 1,500 pages of the police files. The result: the most complete portrait we have of any school shooter. But Vann doesn't stop there. He recounts his own history with guns, contemplating a school shooting. This book is terrifying and true, a story you'll never forget"--Provided by publisher